2009
DOI: 10.1111/j.1469-1809.2009.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

New Mutations of EXT1 and EXT2 Genes in German Patients with Multiple Osteochondromas

Abstract: SummaryMutations in either the EXT1 or EXT2 genes lead to Multiple Osteochondromas (MO), an autosomal dominantly inherited disorder. This is a report on clinical findings and results of molecular analyses of both genes in 23 German patients affected by MO. Mutation screening was performed by using denaturing high performance liquid chromatography (dHPLC) and automated sequencing. In 17 of 23 patients novel pathogenic mutations have been identified; eleven in the EXT1 and six in the EXT2 gene. Five patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…As previously reported in distinct populations (Ciavarella et al, 2013;Delgado et al,2014;Heinritz et al, 2009;Ishimaru et al, 2016;Pedrini et al, 2005; Sarri on et al, 2013) a high number of novel pathogenic variants was also identified in Brazilian patients. Of all 50 different variants found in this study, 31 (62%) were novel with no description in the Multiple Osteochondroma Mutation Database (MOdb) (http://medgen.ua.ac.be/LOVDDv.2.0/home.php).…”
Section: Discussionsupporting
confidence: 77%
“…As previously reported in distinct populations (Ciavarella et al, 2013;Delgado et al,2014;Heinritz et al, 2009;Ishimaru et al, 2016;Pedrini et al, 2005; Sarri on et al, 2013) a high number of novel pathogenic variants was also identified in Brazilian patients. Of all 50 different variants found in this study, 31 (62%) were novel with no description in the Multiple Osteochondroma Mutation Database (MOdb) (http://medgen.ua.ac.be/LOVDDv.2.0/home.php).…”
Section: Discussionsupporting
confidence: 77%
“…This is further supported by the observation that mutant proteins derived from sequences with missense mutations were completely inactive in vitro (McCormick et al, 1998). Missense mutations are obviously important, as shown not only by the severity of phenotypes in our Family 1, but also by cases and families reported elsewhere (Heinritz et al, 2009).…”
supporting
confidence: 61%
“…Several truncated EXT2s have been predicted to be associated with exostosis and/or HME. Heinritz et al [21] described a mutant transcript in a patient with sporadic exostosis, which probably encoded for a shortened EXT2 protein of 688 amino acids. Wu et al [22] predicted that an aberrant mRNA of EXT2 in a patient with HME would produce a truncated protein of 403 amino acids.…”
Section: Discussionmentioning
confidence: 99%